The new rules of lifting for life : an all-new muscle-building, fat-blasting plan for men and women who want to ace their midlife exams - Schuler, Lou (Avery, 2012)
Presents a weight lifting regimen for intermediate athletes in middle-age that balance total-body strength, endurance, mobility, and coordination, and provides pain-free workouts with suggested diet modifications for older athletes.